1999
DOI: 10.1002/(sici)1099-1581(199903)10:3<151::aid-pat855>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐ and pH‐sensitive amphiphilic gels of copolymers of vinyl ether of ethylene glycol

Abstract: Novel thermo-sensitive linear and crosslinked copolymers of vinyl ether of ethylene-glycol and vinyl butyl ether have been synthesized by gamma-irradiation copolymerization. The effect of comonomer hydrophobicity, neutral salts addition and nature of cations and anions on the position of lower critical soluble temperature of water-soluble copolymers and swelling-deswelling behavior of networks is demonstrated. The combination of thermosensitivity and pH sensitivity of hydrogels are realized in the case of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Similar behaviour has been previously reported for copolymers of VBE with HEA [20] and hydrophilic vinyl ethers. [17][18][19] Complex Formation of the Synthesised Copolymers with PAA Previously, [23] we have demonstrated that the homopolymer PHEA forms hydrogen-bonded interpolymer complexes (IPCs) with PAA in aqueous solutions at low pH. However, the stability of these complexes is relatively low and increase in pH results in the dissociation of IPC.…”
Section: Temperature-responsive Properties Of the Synthesised Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behaviour has been previously reported for copolymers of VBE with HEA [20] and hydrophilic vinyl ethers. [17][18][19] Complex Formation of the Synthesised Copolymers with PAA Previously, [23] we have demonstrated that the homopolymer PHEA forms hydrogen-bonded interpolymer complexes (IPCs) with PAA in aqueous solutions at low pH. However, the stability of these complexes is relatively low and increase in pH results in the dissociation of IPC.…”
Section: Temperature-responsive Properties Of the Synthesised Copolymersmentioning
confidence: 99%
“…Earlier similar random copolymers were synthesised by us using copolymerisation initiated by gamma-radiation. [17][18][19] The copolymerisation of hydrophobic vinyl ether with hydrophilic vinyl ether may result in the preparation of thermosensitive system but the synthesis of these copolymers is rather complicated and requires using protection/deprotection chemistry or ionising radiation. From practical point of view this kind of synthesis is quite costly and the possibility to find a new hydrophilic monomer-hydrophobic monomer pair, which exhibits temperature-sensitivity and can be easily copolymerised is rather challenging.…”
Section: Introductionmentioning
confidence: 95%
“…Linear and crosslinked copolymers of vinyl ethers can be synthesized by radiation polymerization as they belong to hard polymerization monomers, owing to their low reactivity (Mun et al, 1999). Copolymers of a vinyl ether of ethylene glycol and butyl vinyl ether containing both hydrophilic and hydrophobic groups exhibit a thermoresponsive character, owing to the strengthening of the hydrophobic interactions with increasing temperature (Mun et al, 1999).…”
Section: Synthesis Of Egve-bve Hydrogelsmentioning
confidence: 99%
“…Recently, vinyl ether based monomers were polymerized by g-irradiation to produce thermoresponsive gels with any desired temperature transition (Gu¨mu¨s -dereli˙og˘lu et al, 2004;Mun et al, 1999) and were used to control the cell attachment/detachment behaviour by temperature changes (Gu¨mu¨s -dereli˙og˘lu and Karakec -ili˙, 2003). The wettability of water-swellable copolymers of vinyl ethers significantly changes with temperature and this change initiates the cell detachment from the polymeric surface (Gu¨mu¨s -dereli˙og˘lu and Karakec -i˙li, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation